BS EN IEC 62841-3-15:2022 AMD A. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 3-15. Particular requirements for transportable magnetic drills (22nd September 2022) - British Standards Institution,
No abstract available